2020
DOI: 10.1186/s12935-020-01460-z
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish xenograft model of human lung cancer for studying the function of LINC00152 in cell proliferation and invasion

Abstract: Background: Numerous studies have shown that long noncoding RNAs play important roles in human cancer progression. Although zebrafish xenografts have recently become a novel in vivo model for human cancer research, whether such models can be used to study the function of long noncoding RNAs remains unknown. Methods: In vitro studies validated the roles of LINC00152 in the proliferation and invasion of lung cancer cells. In vivo studies of zebrafish xenografts also confirmed these roles of LINC00152. In vivo co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(64 reference statements)
0
18
0
Order By: Relevance
“… [ 135 ] Lung cancer Xenograft model In the zebrafish xenograft model, knockdown of LINC00152 reduced the proliferation and migration of lung cancer cells and enhanced the inhibition effect of afatinib for lung cancer progression in cultured cells and the zebrafish xenograft model. [ 69 ] Lung cancer Xenograft model BPIQ-induced anti-lung cancer is involved in mitochondrial apoptosis. BPIQ could be a promising anti-lung cancer drug for further applications.…”
Section: Zebrafish Modelmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 135 ] Lung cancer Xenograft model In the zebrafish xenograft model, knockdown of LINC00152 reduced the proliferation and migration of lung cancer cells and enhanced the inhibition effect of afatinib for lung cancer progression in cultured cells and the zebrafish xenograft model. [ 69 ] Lung cancer Xenograft model BPIQ-induced anti-lung cancer is involved in mitochondrial apoptosis. BPIQ could be a promising anti-lung cancer drug for further applications.…”
Section: Zebrafish Modelmentioning
confidence: 99%
“…In order to improve the diagnosis and treatment of lung cancer, it is necessary to further understand the pathogenesis and related molecular mechanism of lung cancer. Shen et al 69 established a xenotransplantation model after LINC00152 knockout lung cancer cells were implanted into zebrafish. The comparison between the control group and stereoscopic microscope showed that the silencing of LINC00152 could inhibit the proliferation and metastasis of lung cancer cells.…”
Section: Zebrafish Modelmentioning
confidence: 99%
“…The similarities in the immune cells, cytokines, and the presence of various receptors that are required for host-pathogen interactions makes the correlation of zebrafish research to humans, very much relevant ( Targen et al, 2020 ). Xeno-transplantation was achieved by introducing human lung epithelial A549 cells into the swim bladder of the fish ( Shen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated the ceRNA mechanism of different lncRNAs in HCC metastasis, such as HULC/miR-372/PRKACB, LINC00974/miR-642/KRT19, AGAP2-AS1/miR-16-5p/ANXA11, and so on [19][20][21][22]. Zebra sh xenograft can offer the fast and intuitive metastasis model in cancer research for lncRNA study [23], which prompts us to explore its application in veri cation of ceRNA network in cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%